2021
DOI: 10.1134/s0965545x21050023
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Clay Nanocomposites: Exfoliation and Intercalation of Organophilic Montmorillonite Nanofillers in Styrene–Limonene Copolymer

Abstract: Nanocomposites from Styrene-Limonene copolymers and Algerian organophilic-clay named Maghnite-CTA + (Mag-CTA + ), were prepared by in-situ polymerization using different amounts (2, 5, and 10% by weight) of clay and Azobisisobutyronitrile (AIBN) as a catalyst. The Mag-CTA + is an organophilic silicate clay prepared through a direct exchange process, using Cetyltrimethylammonuim bromide (CTAB) in which it used as green nano-filler. The preparation method of nanocomposites was studied in order to determine and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Araujo et al confirmed the intercalation as well as the exfoliated structure of the clay-based polyamide 6 nanocomposite [29]. Hadj-Hamou and Yahiaoui synthesized antimicrobial poly ( -caprolactone) (PCL), poly (vinyl chloride) (PVC) and organo-clay nanobioblended films through the melt blending method, where the nanocomposite showed a mixed intercalated/partially exfoliated structure [39].…”
Section: Thermogravimetric Analysis Of Clay Before and After Modifica...mentioning
confidence: 94%
See 1 more Smart Citation
“…Araujo et al confirmed the intercalation as well as the exfoliated structure of the clay-based polyamide 6 nanocomposite [29]. Hadj-Hamou and Yahiaoui synthesized antimicrobial poly ( -caprolactone) (PCL), poly (vinyl chloride) (PVC) and organo-clay nanobioblended films through the melt blending method, where the nanocomposite showed a mixed intercalated/partially exfoliated structure [39].…”
Section: Thermogravimetric Analysis Of Clay Before and After Modifica...mentioning
confidence: 94%
“…There was no significant characteristic diffraction peak of pure PVC polymer films, which was found due to the amorphous nature of the PVC polymer (Figure3D).Araujo et al confirmed the intercalation as well as the exfoliated structure of the clay-based polyamide 6 nanocomposite[29]. Hadj-Hamou and Yahiaoui synthesized antimicrobial poly ( -caprolactone) (PCL), poly (vinyl chloride) (PVC) and organo-clay nanobioblended films through the melt blending method, where the nanocomposite showed a mixed intercalated/partially exfoliated structure[39].Based on the above observation, it can be concluded that there was a strong interaction between the inorganic filler and PVC polymer.…”
mentioning
confidence: 95%
“…In (Hodhaifa et al, 2021) the use of bentonite clays for drilling wells was studied because they have good hydrophilic and dispersing properties. Montmorillonite, which is the basis for bentonite powder, is one of the most active ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…The uniqueness of our research lies in the fact that methods for superhydrophobizing montmorillonite from Tagan deposits have not previously been used. Results from our previous studies were presented in an article published in 2021 (Hodhaifa et al, 2021), where octadecylamine was used as the superhydrophobic agent, with a contact angle of 157 degrees.…”
Section: Introductionmentioning
confidence: 99%